A Decade of JAK Inhibitors: What Have We Learned and What May Be the Future?. Issue 12 (2nd November 2021) - Liu, Christine; Kieltyka, Jacqueline; Fleischmann, Roy; Gadina, Massimo; O'Shea, John J.
Abstract : The discovery of cytokines and their role in immune and inflammatory disease led to the development of a plethora of targeted biologic therapies. Later, efforts to understand mechanisms of cytokine signal transduction led to the discovery of JAKs, which themselves were quickly identified as therapeutic targets. It has been a decade since the first JAK inhibitors (jakinibs) were approved, and there are now 9 jakinibs approved for the treatment of rheumatic, dermatologic, hematologic, and gastrointestinal indications, along with emergency authorization for COVID‐19. In this review, we will summarize relevant discoveries that led to first‐generation jakinibs and review their efficacy and safety as demonstrated in pivotal clinical studies. We will discuss the next generation of more selective jakinibs, along with agents that target kinase families beyond JAKs. Finally, we will reflect on both the opportunities and challenges ahead as we enter the second decade of the clinical use of jakinibs.